PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP KINERJA MANAJEMEN KEUANGAN UMK: (Studi Pelaku Usaha Mikro Bidang Kuliner di Kota Surabaya) - Ute Ch. Nasution; Akbar Nugroho (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469), 2021)
MSMEs are one of the main actors in the development of a country's economic sector. The resilience of MSMEs is proven by the ability to withstand the existing financial crises. However, the development of MSMEs is hampered by several internal and external problems, with one of the main problems being the low awareness of business actors about financial management. Good financial management is influenced by several factors, where the focus in this study is the financial literacy factor and financial attitude owned by MSE’s (Micro and Small Enterprises). Good financial literacy will make business people able to utilize knowledge in the field of finance in making the right decisions in improving their business performance. While a good financial attitude can improve an individual's behavior towards the money he has. So the author is interested in compiling a study entitled "The Influence of Financial Literacy and Financial Attitudes on the Performance of Umk Financial Management (Study of Micro Business Actors in The Culinary Field in Surabaya City). The purpose of this study is to find out the influence of financial literacy and financial attitudes on the performance of MSE’s financial management. This type of research is quantitative, using the "purposive sampling" sampling method, which is the determination of samples with certain considerations or criteria. The number of samples used in this study was 100 respondents. Data collection techniques use questionnaires that respondents can access through Google Form. This study shows the results that Financial Literacy and Financial Attitudes have a positive and significant effect on Financial Management Performance.